Classical and general relativistic post-Keplerian effects in binary pulsars hosting fast rotating main sequence stars - Iorio, Lorenzo; Rieutord, Michel; Rozelot, Jean-Pierre; de Souza, Armando Domiciano (The European physical journal. C, Particles and fields, 2019)
We consider a binary system composed of a pulsar and a massive, fast rotating, highly distorted main sequence star of mass M , spin angular momentum S , dimensionless mass quadrupole moment J 2 , equatorial and polar radii R e , R p , flattening ν ≐ ( R e - R p ) / R e , and ellipticity ε ≐ 1 - R p 2 / R e 2 as a potential scenario to dynamically put to the test certain post-Keplerian effects of both Newtonian and post-Newtonian nature. We numerically produce time series of the perturbations Δ δ τ of the Rømer-like, orbital component of the pulsar’s time delay δ τ induced over 10 years by the pN gravitoelectric mass monopole Schwarzschild , G M c - 2 , quadrupole G M R e 2 J 2 c - 2 , gravitomagnetic spin dipole Lense - Thirring , G S c - 2 and octupole G S R e 2 ε 2 c - 2 accelerations along with the Newtonian quadrupolar G M R e 2 J 2 one. We do not deal with the various propagation time delays due to the travelling electromagnetic waves. It turns out that, for a Be-type star with M = 15 M ⊙ , R e = 5.96 R ⊙ , ν = 0.203 , S = 3.41 × 10 45 J s , J 2 = 1.92 × 10 - 3 orbited by a pulsar with an orbital period P b ≃ 40–70 days, the classical oblateness-driven effects are at the ≲ 4 - 150 s level, while the pN shifts are of the order of ≲ 1.5 - 20 s G M c - 2 , ≲ 10 - 40 ms G M R e 2 J 2 c - 2 , ≲ 0.5 - 6 ms G S c - 2 , ≲ 5 - 20 μ s G S R e 2 ε 2 c - 2 , depending on their orbital configuration. The root-mean-square (rms) timing residuals σ τ of almost all the existing non-recycled, non-millisecond pulsars orbiting massive, fast rotating main sequence stars are ≲ ms . Thus, such kind of binaries have the potential to become interesting laboratories to measure, or, at least, constrain, some Newtonian and post-Newtonian ( G M c - 2 , G M J 2 c - 2 , and, perhaps, G S c - 2 as well) key features of the distorted gravitational fields of the fast rotating stars hosted by them.